Gêmeos, subjetividade e narcisismo: especificidades interferentes - Marquez, Ilcéa Sônia Maria de Andrade Borba (2008)
The objective of this study is to clarify the twin births specificity and possible consequences either on parental imaginary or in the proper twin. It is an unusual situation, where one ovule is divided in two, causing, then, the creation of two identical human beings: exactly the same sanguineous group, physical enzymes, proteins, physical characteristics and pathological trends: human being in duplicate. This situation represents another challenge for the parents in the performance of maternity and paternity proper tasks. The double births guide them to life mysteries - the reproduction and the intrauterine space. When parents stand out the equal equalities in their choices of similar names, clothes and toys, actually they are denying the pair, considering them as if they were only one such attitudes lead to future consequences For the proper twin, it represents one more difficulty related to the achievement of a unique and singular identity, since they mutually follow themselves, without being illusion or hallucination. As a result they face some questions: Which are the consequences of living in the privacy of the identical and having to compose and recognize themselves as exterior and different? How to obtain a proper place in their parents desire, the family and later in the social environment, in spite of the false recognizing and the confusions of all, incapable of a steady differentiation? This present study is based on the thought of Sigmund Freud and other psychoanalyst authors, as, Otto Rank, André Green, Jacques Lacan, René Kaes, Joyce McDougall, Eduardo Braier, Beatriz Salzberg, Bernard Tanis, Renato Mezan, Maria Rita Kehl and others who contribute for the clarification of the questions involving twins: the specular images, the shadows, spirits, the idea of soul, the strange question about the double and identical, the narcissism experience and the fraternity complex. The used method is the conceptual analysis of the selected texts and clinical material placed in discussion and it has the Psychoanalyst Clinic as elementary and purpose